THE EFFECTIVENESS OF MARRIAGE AGE RESTRICTION (Case Study in Cianjur and Ngamprah West Java in 2019-2020) - Nur Hidayat; Abdul Jalil (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2023)
Abstract. The dynamics of the development of family law in Indonesia continues. Problems with family law are increasingly varied. To accommodate and overcome this, it is necessary to have a legal breakthrough. Marriage Law number 1 of 1974 is one of the reference rules that regulate marriage in Indonesia with all its problems. To be able to keep up with the dynamics of the times, Law Number 1 of 1974 has undergone changes. This change can be seen with the enactment of Law number 16 of 2019 concerning marriage on October 14, 2019 and comes into force on October 15, 2019. This change is more about the minimum age limit when getting married. Where previously the minimum age limit for women was 16 years while for men it was 19 years when they were about to get married. After the enactment of Law Number 16 of 2019 amendments to Law Number 1 of 1974 concerning marriage, the minimum age limit between men and women who will marry is 19 years. After the enactment of Law number 16 of 2019 as an amendment to law number 1 of 1974 concerning marriage on October 15, 2019, it is necessary to conduct a study related to the effectiveness of the amendment to the law, to find out the extent of the impact of the amendment to the law. in society.